55‐4: XTPL approach to print conductive structures in microscale for next‐generation displays. Issue 1 (29th May 2019) - Wiatrowska, Aneta; Kowalczewski, Piotr; Dusza, Michał; Zięba, Maciej; Fiączyk, Karolina; Cichoń, Przemysław; Fijak, Krzysztof; Granek, Filip
Abstract : Printing a wide range of nanomaterials and making the process scalable is the central problem for industries that are shaping the technological landscape of the XXI century. In this regard, the XTPL technology can be transforming for display industry. We mainly focus on three key aspects: repair of open defects, fabrication of transparent conductive films (TCFs), and deposition of quantum dots, which offers tremendous advantages of additive manufacturing.